Influence of nano-CuO modification on crystallization behavior and surface characteristics of P2O5 containing Li2O-ZnO-B2O3-SiO2 glass-ceramics - Copoglu, Nurullah; Daloglu, Sinan; Karaahmet, Oguz; Cicek, Bugra (ELSEVIER SCIENCE SA, 2024)
This paper investigates the impact of nano-CuO addition on the crystallization process and surface properties of phosphate containing lithium zinc borosilicate glass-ceramic coatings. A comprehensive analysis was performed using diverse thermal, structural, and morphological techniques such as hot stage microscope, differential thermal analysis, X-ray diffraction analysis and scanning electron microscopy. Thermal analysis revealed a glass transition temperature of 478.5 degrees C and a crystallization onset temperature of 595.6 degrees C. The coefficient of thermal expansion was measured to be 8.94 x 10-6.degrees C-1. Viscosity measurements indicated a significant decrease in viscosity with increasing temperature, following the Vogel-Fulcher-Tammann equation. Kinetic studies revealed an activation energy of 11.36 kJ/mol for the crystallization process, suggesting potential kinetic hindrance for the reference glass-ceramic coating. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses confirmed the formation of a crystalline phases of Li2ZnSiO4 and Li3PO4 at crystallization temperatures above 750 degrees C. Nano-CuO addition was found to promote crystal formation and increase the inter-crystal spacing according to the SEM analysis. Optical microscopy and 3D surface analysis revealed that nano-CuO addition refined surface texture and reduced the surface roughness of the glass-ceramic coatings at varying crystallization temperatures of 750, 800 and 850 degrees C. Moreover, contact angle measurements indicated that nano-CuO addition decreased the wetting angle of the coatings around 62 %, suggesting improved hydrophilicity. The findings suggest that nano-CuO addition can enhance the crystallization kinetics and improve the surface quality and hydrophilicity of glass-ceramic coatings.
Keywords: Glass -ceramic; Crystallization kinetics; Surface roughness; Thermal behavior; Coating; GLASS-CERAMIC COATINGS; THERMAL-EXPANSION; MICROSTRUCTURAL CHARACTERIZATION; NONISOTHERMAL CRYSTALLIZATION; PHASE-CHANGE; KINETICS; NUCLEATION; VISCOSITY; ANGLE; TRANSITION; Materials Science; Physics